Police administration - Mohd Adnan, Normala (Cengage Learning, 2008)
In Malaysia, the Royal Malaysian Police or Polis Diraja Malaysia is the inheritor of a long and proud tradition of service to the people. Modelled on the British system, it is a centralised organisation that is assigned the responsibility to implement the law, apprehend the criminal, restore order and preserve peace in the society